Flat Stanley - Brown, Jeff; Nash, Scott (New York HarperCollins, 2006)
"Based on the original Flat Stanley by Jeff Brown"--Verso t.p
A picture book version of the story in which a bulletin board falls on Stanley while he is sleeping, and he finds that being flat has its advantages
Hurg
5
Keywords: Humorous stories